Control of Diaphorina citri (Kuwayama) By Trunk Application of Systemic Insecticide in Young Citrus Plant Before Planting - Sanches, André Luiz; Felippe, Marcos R.; Carmo, Alexandre U.; Rugno, Gabriel R.; Yamamoto, Pedro T. (BioAssay, 2009)
An assay were set up in greenhouse at the Scientific Department of Fundecitrus from march to may 2006 to evaluate the efficiency of systemic insecticides applied via drench in young citrus plant to control of Diaphorina citri (Kuwayama). The applied treatments were: (1) thiamethoxam 250 WG – 0.3 g of a.i./plant, (2) imidacloprid 700 WG – 0.35 g of a.i./plant and (3) Control. The adult psyllids captured in orchards were confined in the treated plants in staged periods from 0 to 30 days after application (DAA), from 31 to 45 DAA, from 46 to 60 DAA and 61 to 80 DAA. The dead insects were counted at 3, 6, 24, 48, 72 and 96 hours after confinement (HAC). The experiments were installed in a completely randomized design. The efficiency of control was calculated by ABBOTT’s formula. Thiamethoxam and imidacloprid showed statistical difference from the control at 3 hours after application in the first and second confinement period. However, in the third and fourth confinement period, the statistical difference was observed only 24 HAC. The efficiency was higher than 95% to the insecticides tested until 80 DAA at the end of 96 hours under confinement.